2009
DOI: 10.1007/s00436-009-1600-0
|View full text |Cite
|
Sign up to set email alerts
|

Gyrodactylus species (Monogenea: Gyrodactylidae) on the cichlid fishes of Senegal, with the description of Gyrodactylus ergensi n. sp. from Mango tilapia, Sarotherodon galilaeus L. (Teleostei: Cichilidae)

Abstract: The first record of Gyrodactylus species Nordmann, 1832 on the cichlid fish from Senegal is reported. Gyrodactylus parasites were found on four host species studied, Hemichromis fasciatus, Hemichromis letournaeuxi, Oreochromis niloticus, and Sarotherodon galilaeus. Gyrodactylus cichlidarum Paperna (Bamidgeh 13:14-29, 1968) were collected from H. fasciatus, and its identity was confirmed based on the morphometrical comparison with the holotype specimens of G. cichlidarum. Only one specimen of Gyrodactylus sp. w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 12 publications
(18 reference statements)
0
18
0
Order By: Relevance
“…As our knowledge of monogenean biodiversity is a clear reflection of previous sampling effort, the predictions of parasite biodiversity in Asia and South America might also be high, following the conservative estimates of Bakke et al (2002). Based on the observations in Přikrylová et al (2009), this research found the hamuli of G. malalai sp. nov., having a slender appearance, morphologically very similar to those of G.nyanzae and G. ergensi.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…As our knowledge of monogenean biodiversity is a clear reflection of previous sampling effort, the predictions of parasite biodiversity in Asia and South America might also be high, following the conservative estimates of Bakke et al (2002). Based on the observations in Přikrylová et al (2009), this research found the hamuli of G. malalai sp. nov., having a slender appearance, morphologically very similar to those of G.nyanzae and G. ergensi.…”
Section: Discussionmentioning
confidence: 78%
“…All measurements are in micrometers unless stated otherwise and presented as mean with a standard deviation and range plus number of measurements in parentheses. For comparative studies of the African species of Gyrodactylus, type material of 14 species were obtained and studied, as mentioned in Přikrylová et al (2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, it is the first parasite to be formally described from this fish species. It brings the total number of Gyrodactylus species described from cichlid hosts to 15 (Paperna 1979;Boeger & Popazoglo 1995;Christison et al 2005;Přikrylová et al 2009Přikrylová et al , 2012García-Vásquez et al 2011;Vanhove et al 2011). Jalali et al (2001) observed that the highly distinct zoogeographical regions of Iran and the high degree of endemicity of its freshwater fishes gave rise to a diverse monogenean fauna.…”
Section: Discussionmentioning
confidence: 99%